Urinary Tract Infection among infants and school aged children: A review - Alenazi, Shehab Ahmed (Pakistan Journal of Medical & Health Sciences, 2024)
A considerable number of bacteria of the same species growing in the urine is known as a urinary tract infection (UTI). Currently, it is thought that the most common cause of a serious bacterial disease in children under the age of two is a febrile urinary tract infection. Boys are more likely than girls to have it in their early years, but after infancy, girls are far more likely to have it. UTIs can be classified into three groups based on their clinical presentations: asymptomatic bacteriuria, lower UTI (cystitis), and upper UTI (acute pyelonephritis). UTI prevalence varies by country, from 6% in industrialized nations to 37% in low-income countries. According to a study conducted in Saudi Arabia, 24% of people had UTIs. In children, gut flora, specifically Escherichia coli and Klebsiella, are the most frequent causal organisms of urinary tract infections. Kidney failure and kidney scarring are among the short- and long-term consequences that need for fast and suitable treatment. There could be a 30 to 50% chance of a return of UTI. This review disucssed UTI prevalence, causes, classifications, complications, and treatment among age groups of infants and school aged children